2008
DOI: 10.1186/1742-4690-5-32
|View full text |Cite
|
Sign up to set email alerts
|

HIV transfer between CD4 T cells does not require LFA-1 binding to ICAM-1 and is governed by the interaction of HIV envelope glycoprotein with CD4

Abstract: Background: Cell-to-cell HIV transmission requires cellular contacts that may be in part mediated by the integrin leukocyte function antigen (LFA)-1 and its ligands intercellular adhesion molecule (ICAM)-1, -2 and -3. The role of these molecules in free virus infection of CD4 T cells or in transinfection mediated by dendritic cells (DC) has been previously described. Here, we evaluate their role in viral transmission between different HIV producing cells and primary CD4 T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 41 publications
2
64
1
Order By: Relevance
“…Interestingly, interactions between LFA-1 and ICAM-1 are also needed to facilitate HIV-1-induced syncytium formation (21,33,63). However, our results are in conflict with data from a recent study demonstrating that although interactions between LFA-1 and ICAM-1 strongly facilitate cell-to-cell contacts that promote HIV-1 transmission, viral transfer between virus-infected effector T cells and quiescent CD4 ϩ T cells can occur even in the absence of LFA-1-ICAM-1 interactions (46). The conclusions made by those authors were based mainly on results obtained by using MOLT T cells as HIV-1 effector cells and primary resting CD4 ϩ T cells as acceptor cells in the presence of anti-LFA-1 or anti-ICAM-1 antibody.…”
Section: Discussioncontrasting
confidence: 57%
“…Interestingly, interactions between LFA-1 and ICAM-1 are also needed to facilitate HIV-1-induced syncytium formation (21,33,63). However, our results are in conflict with data from a recent study demonstrating that although interactions between LFA-1 and ICAM-1 strongly facilitate cell-to-cell contacts that promote HIV-1 transmission, viral transfer between virus-infected effector T cells and quiescent CD4 ϩ T cells can occur even in the absence of LFA-1-ICAM-1 interactions (46). The conclusions made by those authors were based mainly on results obtained by using MOLT T cells as HIV-1 effector cells and primary resting CD4 ϩ T cells as acceptor cells in the presence of anti-LFA-1 or anti-ICAM-1 antibody.…”
Section: Discussioncontrasting
confidence: 57%
“…LFA-1 expression on target cells has been shown to contribute to HIV-1 transmission to CD4 ϩ T cells mediated by DCs (18,20,21) and T cells (22,25,26,37,38). By contrast, a recent study suggested that HIV-1 transfer between CD4 ϩ T cells does not require LFA-1 binding to ICAM-1 and is mediated by the interaction of HIV-1 envelope with CD4 (31). It remains to be examined whether HIV-1 infection of DCs and CD4 ϩ T cells modulates the expression and function of ICAMs and binding ligands.…”
Section: Discussionmentioning
confidence: 88%
“…However, the conformational state, and hence the affinity of LFA-1 to its ligand ICAM-1, modulates susceptibility to HIV infection (9,15,51). Some recent reports demonstrated that the adhesion molecules LFA-1, ICAM-1, and ICAM-3 facilitate VS formation between T cells (2,23), although viral transfer may occur even in the absence of LFA-1 (42). We thus assessed the impact of LFA-1 on HIV replication and polysynapse formation.…”
Section: Resultsmentioning
confidence: 99%